Formação continuada com base na pedagogia Waldorf: contribuições do projeto Dom da Palavra - Salles, Rubens (2010)
The main purpose of this work is to analyze considerations made by 1st grade elementary school teachers, who took part in the "Dom da Palavra" (PDP) ("Gift of the Word") project - a continual education development project based on the Waldorf Pedagogic Educational System as to how contributions offered by the proposed pedagogic teaching concepts could help them in regard to their usual teaching methods. As a project based on teaching methods for which there are few academic works, we intend to present herein an extract of its main fundamental elements together with its pedagogic and theoretical basis, the special elements that constitutes the project s main directive, as well as the theoretical foundation for all faculty continual learning system. A descriptive and analytical study of quantitative and qualitative nature was chosen. To obtain the necessary data, structured questionnaires, structured interviews with written and audio-recorded statements, as well as videotaped interviews and activities for further analysis and interpretation of data, were used. On each of the five municipalities where the project was implemented, more than 70% of attendance was obtained from the 125 teachers who completed the training course - with 102 teachers present whenever those evaluations were made, which represents 81.6% of the participants. Through this analysis, we believe the positive evaluation made by teachers who took part in program Dom da Palavra , answered its questionnaires and interviews, was based on how the proposed concepts and practices responded to those teachers real needs and helped them solve daily problems at school. In addition, the training model presented, on how continual education of teachers must be carried out, was made in accordance with concepts and proposals by several important and academically acknowledged authors.